2009
DOI: 10.1590/s1519-69842009000100029
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of albino and melanic variants of Biomphalaria glabrata Say, 1818 (Mollusca: Planorbidae) following infection by Schistosoma mansoni Sambon, 1907

Abstract: The behaviour of the albino and melanic variants of Biomphalaria glabrata of Belo Horizonte (MG. Brazil) was studied comparatively, in terms of their respective susceptibilities to infection by Schistosoma mansoni of the same origin, through observation of the elimination of cercariae for a three-month period and the calculation of mortality and infection rates, in control and in infected snails. The number of amoebocytes, granulocytes and hyalinocytes in the circulating hemolymph during different periods of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This explains our results which showed that granulocytes were significantly higher in the control resistant snails than the corresponding susceptible snails, while hyalinocytes displayed a reverse profile. Allegretti et al [46] attributed the higher resistance of albino B. glabrata snails to S. mansoni infection to their increased granulocytes count. In the same context, Pila et al [47] suggested that high granulocytes' count is related to resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This explains our results which showed that granulocytes were significantly higher in the control resistant snails than the corresponding susceptible snails, while hyalinocytes displayed a reverse profile. Allegretti et al [46] attributed the higher resistance of albino B. glabrata snails to S. mansoni infection to their increased granulocytes count. In the same context, Pila et al [47] suggested that high granulocytes' count is related to resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Variations on the pattern of pigmentation on the molluscs' mantles are genetic and can influence the susceptibility of molluscs (Chquiloff et al, 1978;Allegretti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that the biochemistry of the melanin can interfere in the defense mechanisms of molluscs, so that melanic specimens show higher susceptibility to being infected by the Schistosoma mansoni when compared to albino specimens (Allegretti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be caused by an enzyme deficiency involving the metabolism of melanin during prenatal development (Allegretti et al, 2009). There are two main types of albinism in snails: albino shelled and albino-bodied but the genes responsible for them had not been known.…”
Section: Introductionmentioning
confidence: 99%